EXTRAORDINARY REMEDIES: Effectiveness of General Repercussion Decisions (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
This article deals with the judicial decisions handed down by the Federal Supreme Court on extraordinary appeals with general repercussion and aims to demonstrate how these decisions are binding on the other lower courts. The method used was a hypothetical-deductive approach, based on qualitative research, from a bibliographic review of scientific articles and books that deal with the proposed theme. Thus, the theme begins with an exposition of the standardizing function of extraordinary appeals, then moves on to an analysis of the general repercussion from a historical, conceptual and effects perspective, and finally looks at the binding effects of the general repercussion decision. As a result, it was found that the general repercussion has imprinted the ability to objectify the decision rendered in an extraordinary appeal, legitimating the irradiation of the solution adopted in the paradigmatic case, in relation to other cases that deal with the same issue.Keywords: Supreme Court; uniformity function; extraordinary appeal; general repercussion.